From traditional dry-erase board to virtual context-aware digital whiteboard / Hajar Izzati Mohd Ghazalli - Mohd Ghazalli, Hajar Izzati (2014)
Context-aware is the ability of an application reacts to changes of the environment. Context-aware applications, like smart systems are rapidly developed recently.Unknowingly, context-aware applications are more common in one’s daily life.Traditional dry-erase whiteboard is an example of convention context-aware method in office environment to record staff activities. There are four (4) main problems of the usage of traditional whiteboard in displaying academic staffs’ status in the office: (1) Limited time to update the information. (2) Non-real time information. (3) Limited space to write. (4) No data storage. Therefore, a Context-aware Digital Whiteboard (CAW) is proposed to solve the problems of traditional dry-erase whiteboard in administrator office of Faculty of Computer and Mathematical Sciences (FSKM). The proposed system embeds context-aware elements that able users to be more conscious of what activities currently are going on in the workplace. In summary, the whiteboard is able to report the presence of staffs’ in related activities throughout years.